NLRP3 inflammasome signaling as an early molecular response is negatively controlled by miR-186 in CFA-induced prosopalgia mice - Chen,Ming-lei (2018)
The NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome is the most frequently studied in the central nervous system and has been linked to neuropathic pain. In this study, a post-translational mechanism of microRNA (miR)-186 via regulating the expression of NLRP3 in the complete Freund's adjuvant (CFA)-treated mice was investigated. The injection of CFA was used to induce trigeminal neuropathic pain in mice. miRs microarray chip assay was performed in trigeminal ganglions (TGs). CFA treatment significantly increased the mRNA expression of NLRP3, interleukin (IL)-1β, and IL-18 in TGs compared to the control group. Moreover, 26 miRs were differentially expressed in TGs from trigeminal neuropathic pain mice, and the expression of miR-186 showed the lowest level of all the miRs. Further examination revealed that NLRP3 was a candidate target gene of miR-186. We delivered miR-186 mimics to CFA-treated mice. The head withdrawal thresholds of the CFA-treated mice were significantly increased by miR-186 mimics injection compared with CFA single treatment. The mRNA and protein expression of NLRP3, IL-1β, and IL-18 in TGs from trigeminal neuropathic pain mice were significantly inhibited by miR-186 mimics treatment compared to the CFA group. miR-186 was able to suppress the neuropathic pain via regulating the NLRP3 inflammasome signaling.